KEMAMPUAN MENULIS PANTUN BAHASA DAERAH PADA MAHASIWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA, UNIVERSITAS BATURAJA - Inawati Inawati; Darningwati Darningwati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
: This study aims to describe the ability of second semester students of the Indonesian Language and Literature Education Study Program to write regional language poems. The research method uses descriptive methods. The population is 35 people with a sample of 28 people. The data collection technique was in the form of a test, namely writing rhymes using local languages. Based on the results of the analysis, it shows that: Semester II students of the Indonesian Language and Literature Education Study Program, FKIP Baturaja University, are generally in the category of being able to write rhymes in regional languages. This is because the percentage of test scores obtained by students shows as many as 10 students (35.7%) are included in the very capable category and as many as 10 students (35.7%) are in the capable category. Furthermore, as many as 3 students (10.7%) were included in the fairly capable category, while those included in the poor category were 5 students (17.9%), and none failed (0%), with an average score obtained of 72.57. These results indicate that students' abilities are included in the category of being able to write rhymes using regional languages.